Ore money ore problems: A resource extraction game. Issue 2 (3rd April 2023) - Jacobson, Sarah
Abstract: The economic theory of natural resource exploitation predicts that scarcity crises will not arise because forward-looking resource owners will smooth their extraction over time to maximize their profits. The model providing this result can seem opaque and technical to students, but its intuition can be learned from experience. The author shares a game that provides that experience. Participants play the role of mine owners who must decide how much to extract in each of two periods. In addition to showing how price signals through markets can prevent sudden increases in scarcity, the game also provides lessons about intertemporal choice, market power, information, and property rights. The author provides all materials needed to play the game as is or to customize it for alternative learning outcomes.